DERIVATIVES, RISK MANAGEMENT AND FINANCIAL DISASTERS - Boyle, Phelim P. (Assurances, 2000)
This paper provides a brief introduction to derivative securities and discusses their role in providing efficient allocations of risk within an economic system. Derivatives can be used to increase exposure to particular types of risk. We discuss three recent prominent financial disasters which have been associated to some extent with derivatives usage. These cases concern the demise of Barings Bank, the bankruptcy of Orange County, California and the near collapse of Long Term Capital Management. We emphasize the common elements in each case. We draw on a framework due to David Emanuel to suggest that traditional performance metrics do a poor job of measuring performance of derivative strategies.